2001
DOI: 10.1046/j.1365-3091.2001.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Fault‐controlled dolomitization at Swan Hills Simonette oil field (Devonian), deep basin west‐central Alberta, Canada

Abstract: The partly dolomitized Swan Hills Formation (Middle‐Upper Devonian) in the Simonette oil field of west‐central Alberta underwent a complex diagenetic history, which occurred in environments ranging from near surface to deep (>2500 m) burial. Five petrographically and geochemically distinct dolomites that include both cementing and replacive varieties post‐date stylolites in limestones (depths >500 m). These include early planar varieties and later saddle dolomites. Fluid inclusion data from saddle dolomite cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 32 publications
8
86
0
1
Order By: Relevance
“…These values are significantly higher than any seawater throughout geological time and indicate that the fluids which precipitated the dolomite had interacted with feldspathic siliclastic sediments or basement rocks (e.g. Duggan et al, 2001;Davies and Smith, 2006).…”
Section: Burial Dolomitementioning
confidence: 87%
See 1 more Smart Citation
“…These values are significantly higher than any seawater throughout geological time and indicate that the fluids which precipitated the dolomite had interacted with feldspathic siliclastic sediments or basement rocks (e.g. Duggan et al, 2001;Davies and Smith, 2006).…”
Section: Burial Dolomitementioning
confidence: 87%
“…Some of the cements, notably dolomite and anhydrite, can have a significant impact on reservoir quality, e.g. the Simonette oil field, Swan-Hills Formation (Devonian) Alberta (Duggan et al, 2001), where anhydrite and burial dolomite represent up to 50% of the rock volume. Evidently, some process or processes of concentration has occurred for Mg, Fe, F, Ba, SO 4 2À , SiO 2 , K, Al, Zn, Pb, and Sr, and perhaps analysis of the lower volume cements can offer as much information about the processes involved as the higher volume cements (Esteban and Taberner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The inferred timing of ME dolomite coincided with the Antler Orogeny and a late Paleozoic thermal anomaly, suggesting that the formation of ME dolomite was possibly related to tectonic compression and/or thermal convection of basinal fluids. Previous studies have shown that fault and fracture conduit systems were important in delivering dolomitizing fluids to the Devonian strata in the Western Canada Sedimentary Basin, causing extensive dolomitization (Duggan et al 2001;Green and Mountjoy 2005;Kaufman et al 1991). After the fluids reached the Ratner Formation, lateral migration of dolomitizing fluids along laminations and relatively permeable layers was likely and could explain the locally layered and interlayered distribution of ME dolomite.…”
Section: Dolomitizationmentioning
confidence: 96%
“…Devonian carbonate is an important oil and gas reservoir bed in the Swan Hills, Alberta Basin, Canada. There is ubiquitous dolomitization near the fracture and fluid channel [18] , the cross range distance of affection is about 2 km near the fluid side of the channel [19] , the filling degree and type of the matrix near the crack impact the reservoir bed properties [20] . Some attention has been paid to the transformation of carbonate reservoir bed by faulting, but it is only focused on a specific aspect, for example, a study showed that faulting obviously controlled the Ordovician paleo-karst in the west of the Lunnan area [21] , hydrothermal fluids carried by a mjor fault caused metasomatism of carbonate to form a secondary fluorite belt and improved reservoir bed performance [22] .…”
mentioning
confidence: 99%